Identification, characterization, and engineering of glycosylation in thrombolytics - Toul, Martin; Slonkova, Veronika; Mican, Jan; Urminsky, Adam; Tomkova, Maria; Sedlak, Erik; Bednar, David; Damborsky, Jiri; Hernychova, Lenka; Prokop, Zbynek (Biotechnology advances, 2023)
Cardiovascular diseases, such as myocardial infarction, ischemic stroke, and pulmonary embolism, are the most common causes of disability and death worldwide. Blood clot hydrolysis by thrombolytic enzymes and thrombectomy are key clinical interventions. The most widely used thrombolytic enzyme is alteplase, which has been used in clinical practice since 1986. Another clinically used thrombolytic protein is tenecteplase, which has modified epitopes and engineered glycosylation sites, suggesting that carbohydrate modification in thrombolytic enzymes is a viable strategy for their improvement. This comprehensive review summarizes current knowledge on computational and experimental identification of glycosylation sites and glycan identity, together with methods used for their reengineering. Practical examples from previous studies focus on modification of glycosylations in thrombolytics, e.g., alteplase, tenecteplase, reteplase, urokinase, saruplase, and desmoteplase. Collected clinical data on these glycoproteins demonstrate the great potential of this engineering strategy. Outstanding combinatorics originating from multiple glycosylation sites and the vast variety of covalently attached glycan species can be addressed by directed evolution or rational design. Directed evolution pipelines would benefit from more efficient cell-free expression and high-throughput screening assays, while rational design must employ structure prediction by machine learning and in silico characterization by supercomputing. Perspectives on challenges and opportunities for improvement of thrombolytic enzymes by engineering and evolution of protein glycosylation are provided.
Keywords: Tenecteplase; Tissue Plasminogen Activator; Protein engineering; Glycosylation; Desmoteplase; lidé; Alteplase; Thrombolytic; Cell-free glycoprotein synthesis; tenektepláza; Computational design; fibrinolytika; Urokinase; glykosylace; Myocardial Infarction; tkáňový aktivátor plazminogenu; Fibrinolytic Agents; Biopharmaceutical; infarkt myokardu; Humans